Domestic Devotions in the Early Modern World - Meneghin, Alessia (Intersections, 2018)
This volume sets out to explore the world of domestic devotions and is premised on the assumption that the home was a central space of religious practice and experience throughout the early modern world. The contributions to this book, which deal with themes dating from the fifteenth to the eighteenth century, tell of the intimate relationship between humans and the sacred within the walls of the home. The volume demonstrates that the home cannot be studied in isolation: the sixteen essays, that encompass religious history, the histories of art and architecture, material culture, literary history, and social and cultural history, instead point individually and collectively to the porosity of the home and its connectedness with other institutions and broader communities